Modulating ultrasound contrast generation from injectable nanodroplets for proton range verification by varying the degree of superheat. Issue 4 (11th March 2021) - Heymans, Sophie V.; Carlier, Bram; Toumia, Yosra; Nooijens, Sjoerd; Ingram, Marcus; Giammanco, Andrea; d'Agostino, Emiliano; Crijns, Wouter; Bertrand, Alexander; Paradossi, Gaio; Himmelreich, Uwe; D'hooge, Jan; et al.
Abstract : Purpose: Despite the physical benefits of protons over conventional photon radiation in cancer treatment, range uncertainties impede the ability to harness the full potential of proton therapy. While monitoring the proton range in vivo could reduce the currently adopted safety margins, a routinely applicable range verification technique is still lacking. Recently, phase‐change nanodroplets were proposed for proton range verification, demonstrating a reproducible relationship between the proton range and generated ultrasound contrast after radiation‐induced vaporization at 25°C. In this study, previous findings are extended with proton irradiations at different temperatures, including the physiological temperature of 37°C, for a novel nanodroplet formulation. Moreover, the potential to modulate the linear energy transfer (LET) threshold for vaporization by varying the degree of superheat is investigated, where the aim is to demonstrate vaporization of nanodroplets directly by primary protons. Methods: Perfluorobutane nanodroplets with a shell made of polyvinyl alcohol (PVA‐PFB) or 10, 12‐pentacosadyinoic acid (PCDA‐PFB) were dispersed in polyacrylamide hydrogels and irradiated with 62 MeV passively scattered protons at temperatures of 37°C and 50°C. Nanodroplet transition into echogenic microbubbles was assessed using ultrasound imaging (gray value and attenuation analysis) and optical images. The proton range was measured independently and compared to the generated contrast. Results: Nanodroplet design proved crucial to ensure thermal stability, as PVA‐shelled nanodroplets dramatically outperformed their PCDA‐shelled counterpart. At body temperature, a uniform radiation response proximal to the Bragg peak is attributed to nuclear reaction products interacting with PVA‐PFB nanodroplets, with the 50% drop in ultrasound contrast being 0.17 mm ± 0.20 mm (mean ± standard deviation) in front of the proton range. Also at 50°C, highly reproducible ultrasound contrast profiles were obtained with shifts of −0.74 mm ± 0.09 mm (gray value analysis), −0.86 mm ± 0.04 mm (attenuation analysis) and −0.64 mm ± 0.29 mm (optical analysis). Moreover, a strong contrast enhancement was observed near the Bragg peak, suggesting that nanodroplets were sensitive to primary protons. Conclusions: By varying the degree of superheat of the nanodroplets' core, one can modulate the intensity of the generated ultrasound contrast. Moreover, a submillimeter reproducible relationship between the ultrasound contrast and the proton range was obtained, either indirectly via the visualization of secondary reaction products or directly through the detection of primary protons, depending on the degree of superheat. The potential of PVA‐PFB nanodroplets for in vivo proton range verification was confirmed by observing a reproducible radiation response at physiological temperature, and further studies aim to assess the nanodroplets' performance in a physiological environment. Ultimately, cost‐effective online or offline ultrasound imaging of radiation‐induced nanodroplet vaporization could facilitate the reduction of safety margins in treatment planning and enable adaptive proton therapy. Abstract :